Rare Tumors Presenting as a Mastoid Mass - Lee, Jiyeon; Han, Kyujin; Kim, Chang-Hee (Case Reports in Otolaryngology, 2020)
In terms of diagnosis, a painless isolated mass lesion around the mastoid area is rarely encountered in general practice. In the present study, we report two cases of painless benign mastoid tumors located in the postauricular region. The first patient visited our department with a painless progressing mass lesion behind the right ear, which was later revealed as an intramuscular lipoma in the mastoid origin site of the sternocleidomastoid muscle. The second patient similarly presented to our department with a chief complaint of a painless, palpable mass in the mastoid region. Biopsy results confirmed the diagnosis of an osteoma. In both cases, the tumor was surgically removed by a postauricular approach. Although osteoma and lipoma are benign tumors rarely involved in the mastoid area, presenting without symptoms, it is recommended of complete excision, especially in cases with symptoms or cosmetic deformity.